WHAT CAUSED LAND ABANDONMENT IN VALIGAMAM, NORTH OF JAFFNA, SRI LANKA?: A SPATIAL AND ECONOMETRIC ANALYSIS - Varnika, S.; Neruja, N.; Thanushan, R. (Sri Lanka Forum of University Economists, 2025)
This study aimed to provide a comprehensive understanding of the interplay between population density, migration, and land abandonment in the Valigamam North region, which was profoundly affected by historical events, notably the ethnic conflict in the Jaffna Peninsula from 1987 to 1995. With a randomly selected sample of 85 households, Probit and Tobit models were utilised as analytical tools. Furthermore, this study used thematic mapping methodology with ArcMap 10.4 software. The results of the probit model revealed a statistically significant impact of migration, gender, and income on land abandonment. Conversely, variables such as land size, labour, and loans did not exhibit a statistically significant influence on land abandonment. The findings from the Tobit model indicate a positive correlation between migration and the likelihood of land being abandoned. The results elucidate significant spatial variations, particularly in locales characterised by low population density, where abandonment of land is more prevalent. The outcomes of this research offer insights for the formulation of land management strategies and policy development.
Keywords: Valigamam North; Tobit model; Probit model; Spatial analysis; Land abandonment; Migration